FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN DAN PENERIMAAN TEKNOLOGI PADA SISTEM UJIAN ONLINE - Popon Handayani (LPPM Universitas Bina Sarana Informatika, 2013)
Online Examination System is highly prevalent among all education. One of the private collegesthat participate realize is STMIK NUSA MANDIRI. Implemented in reaction to the self-users, inthe form of acceptance or rejection. Acceptance of a technology is strongly influenced by thereadiness of the users of these technologies, it has been demonstrated empirically by Walczuch etal (2007). Adapting from these studies and research supporting the study entitled